ANTIMAGIC LABELING OF DIGRAPHS - Moviri, Nalliah (IndoMS, 2016)
AbstractAn antimagic labeling of a digraph D with p vertices and q arcs is a bin f from the set of all arcs to the set of positive integers such that all the p oriented vertex weights are distinct, where an oriented vertex weight is the sum of the labels of all arcs entering that vertex minus the sum of the labels of all arcs leaving it. A digraph D is called antimagic if it admits an antimagic labeling. In this paper we investigate the existence of antimagic labelings of some few families of digraphs using hooked Skolem sequences.DOI :Â http://dx.doi.org/10.22342/jims.22.1.216.61-69